Bibliometric Analysis of Islamic Finance - Bollani, Luigi; Chmet, Federico (European Journal of Islamic Finance, 2020)
Islamic finance and Islamic banking have been the subject of central scientific interest, as demonstrated by the significant increase in publications on the subject in recent years. In the present paper, the use of the bibliometric analytical technique is proposed to examine the research on Islamic finance. The objective of the study consists in carrying out a bibliometric analysis of all the publications on Scopus relative to Islamic finance. The parameters used include the type of document (article), the language of publication (English). Among other things, the author, the publication models, the distribution of the thematic category, the distribution of the author’s key words, the country of publication and the most frequently cited article are analyzed. The different rankings reinforce the fact that bibliometric understanding of scientific impact is a multidimensional construct. However, the bibliometric analysis does not take place in an institutional and political vacuum. The institutional context of quality evaluation of public and private research increasingly determines which metrics are applied, with consequent effects on performance evaluation. Through analysis, citation rates are proposed, and the impact factors of journals are quantitative and objective indicators directly linked to published science. The objective of this paper is to identify the future trend of research in the field of Islamic finance.